A research on thermoelectric generator's electrical performance under temperature mismatch conditions for automotive waste heat recovery system. (March 2015) - Tang, Z.B.; Deng, Y.D.; Su, C.Q.; Shuai, W.W.; Xie, C.J.
Abstract: The thermoelectric generators recover useful energy by the function of thermoelectric modules which can convert waste heat energy into electricity from automotive exhaust. In the actual operation, the electrical connected thermoelectric modules are operated under temperature mismatch conditions and then the problem of decreased power output causes due to the inhomogeneous temperature gradient distribution on heat exchanger surface. In this case study, an individual module test system and a test bench have been carried out to test and analyze the impact of thermal imbalance on the output electrical power at module and system level. Variability of the temperature difference and clamping pressure are also tested in the individual module measurement. The system level experimental results clearly describe the phenomenon of thermoelectric generator's decreased power output under mismatched temperature condition and limited working temperature. This situation is improved with thermal insulation on the modules and proved to be effective.